Pengelolaan Sumber Daya Air Lokal: Pemanfaatan Mata Air RT 7 Kelurahan Sumber Rejo, Kota Balikpapan Sebagai Alternatif Sumber Air Bersih Berkelanjutan - Maulani, Melisa Triandini; Febrianti, Nia; Noor Hayati, Rina; Awaliyah, Lia; Arrohman, Maulana Khafid (SPECTA Journal of Technology, 2026)
The need for clean water is one of the essential aspects of community life, especially in areas that are not fully served by the PDAM (Regional Drinking Water Company) distribution network. In Sumber Rejo Subdistrict, particularly in RT 7, the availability of clean water remains a major issue due to the hilly topography, making it difficult for the PDAM pipeline network to reach the area. The local community relies on springs as an alternative water source, which is collected manually without a planned distribution system. This study aims to analyze the potential of the spring in RT 7, Sumber Rejo Subdistrict, as a clean water source based on water quality, flow rate classification, and clean water distribution system planning. The methods used include water quality analysis through laboratory tests covering physical, chemical, and microbiological parameters, flow rate classification based on spring discharge measurements, and distribution system planning using EPANET 2.2 software. The results show that the spring water quality does not fully meet the clean water quality standards according to the Indonesian Ministry of Health Regulation Number 2 of 2023 on Environmental Health, particularly for nitrate, manganese, and aluminum parameters. Based on the flow rate measurements, the spring falls into Class VI, with a flow rate ranging from 0.1 to 1 liter per second, indicating low flow capacity and generally only sufficient to meet water needs on a limited scale (less than 1,000 people). In the clean water distribution network simulation, three alternative distribution scenarios were evaluated, with Alternative 2 showing the most optimal results, with flow velocities ranging from 0.31 to 0.46 m/s